Presenting Natures, Factors and Security Implications of Farmland Related Interhousehold Conflict in South Wollo Evidences from Jamma Woreda - Teshome, Mulugeta Tesfaye (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2018)
The focus of this study is investigating and analyzing different factors of inter-household conflict over land and assessing its human security implications on the study area community. Farmers, in the study area, are suffering from land related conflict and its associated impacts. Descriptive-case study qualitative approach employed in the study. In-depth interview with key informants and FGDs were data collection instruments. Secondary data like archive documents and government reports also used. The finding of the study indicated that inter-household conflict over farmland occurred with the interface of underlined factors and risk factors. Boundary encroachment, land eviction, inherited land conflict, contract breaching conflict are the common one. The divisive land administration institutions, individuals’ unproductive competition over farmland, poorly implemented land administration programs, and cultural attachment to land identified as underlined factors for the farmland conflicts to happen. The culture of violence, the availability of small arms and light weapons, and prevalence of other forms of social conflict are also risk factors, which create fragile peace among the members of the community. The conflict affects the economic, social, political, and psychological wellbeing of the study area residents. It poses economic, social, political, environmental, and human security threats too. It is imperative to revise and harmonize land administration laws if not changing some faultily legislated articles. Above all digital land registration and data administration should considered by governmental organizations and NGOs who are working in land administration sector.